Modelling the Electricity Consumption in a Manufacturing Company through Probability Distribution - Michalková Mária; Pobočíková Ivana; Sedliačková Zuzana (MATEC Web of Conferences, 2022)
The paper deals with model of electricity consumption in a company providing hot and cold forming. As modelled data, there were used hourly records of electricity consumed in the manufacturing processes. The data covered working hours over a year. The probability distributions, chosen for modelling, were normal distribution, gamma distribution, logistic distribution, Weibull distribution and Rayleigh distribution. The goodness of fit of these distributions was judged based on the values of the information criteria (AIC, AICc and BIC), coefficient of determination (R2) and the root mean square error (RMSE). According to these criteria, the best fit was achieved by the two-parameter Weibull distribution.